The life and legend of leadbelly - Wolfe, Charles K. (Da Capo Press, 1999)
Huddie Ledbetter (1889–1949), known to millions of fans simply as Leadbelly, was arguably the most famous black singer in American history. He helped lay the foundations for blues, modern folk music, and rock 'n' roll. This definitive biography draws on a wealth of new archival material, interviews, and previously unknown recordings to detail Leadbelly's proud, tumultuous, and often violent life